Tax Principles According to Abu Yusuf and Adam Smith: Comparative Study - Khurun'in Zahro'; Nuriwanda Azizah Nugraheni; Ishma Amelia; Muhammad Reyhan (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2023)
Taxes are important for every country because it is the main income for the state, which is certainly very influential on state coffers in addition to gain in other fields. In the history of Islam itself, taxes have existed since the time of the Prophet (peace be upon him), and many Muslim scholars poured their thoughts into taxation. One of them is quite famous is Abu Yusuf, who poured a lot of economic thought into his book Al-Kharaj. One of these Western economists is Adam Smith, more commonly known as the Father of Economics. Adam Smith poured much of his thoughts on economics into his book An Inquiry into The Nature and Causes of the Wealth of Nations. The purpose of this study was to know the thoughts of Abu Yusuf and Adam Smith in the principle of taxes as well as to know the similarities and differences in the principle of taxes. This study uses comparative descriptive qualitative research conducted by studying literature or documentation and analyzing data submitted by Miles and Huberman. The results of this study showed that the difference between Abu Yusuf and Adam Smith is very clearly seen, in the taxes levied, Abu Yusuf did not collect taxes on land rent, rent, and wage taxes. And Abu Yusuf strongly emphasized justice where taxes are imposed on the taxpayer in accordance with his ability and does not burden the taxpayers.